Synchrotron radiation microbeam X-ray diffraction for nondestructive assessments of local structural properties of faceted InGaN/GaN quantum wells. (29th January 2018) - Sakaki, Atsushi; Funato, Mitsuru; Kawamura, Tomoaki; Araki, Jun; Kawakami, Yoichi
Abstract: Synchrotron radiation (SR) X-ray diffraction with a sub-µm spatial resolution is used to nondestructively evaluate the local thickness and alloy composition of three-dimensionally faceted InGaN/GaN quantum wells (QWs). The (0001) facet QW on a trapezoidal structure composed of (0001), , and facets is nonuniform, most likely owing to the migration of adatoms between facets. The thickness and composition markedly vary within a short distance for the facet QW of another pyramidal structure. The QW parameters acquired by SR microbeam X-ray diffraction reproduce the local emission property assessed by cathodoluminescence, thereby indicating the high reliability of this method.